ASSESSING THE UTILISATION OF INFORMATION AND COMMUNICATION TECHNOLOGY TOOLS FOR TEACHING SECONDARY SCHOOLS ISLAMIC STUDIES IN ILORIN, NIGERIA - Jibril Olaniyi Ayuba; Lawal Abiola Abdullateef; Fathor Rozi; Fathor Rosi; Agus Nu'man (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
The study aims to examine the utilisation of ICT tools for teaching secondary schools Islamic studies in Ilorin, Nigeria. Descriptive research design was adopted and simple random technique was adopted to select 120 Islamic Studies teachers in Ilorin. Researcher self-designed questionnaire was used to elicit information from the respondents. Two research questions were raised and answered using percentage. The findings of the study revealed that ICT have influence on teaching and learning. Also, result of the findings shows computer system, telephone, Mp3 player are available for teaching and learning Islamic Studies while firm projector, T.V set, film stripe are not available. The findings also revealed that majority of Islamic Studies teachers are not using ICT tools to teach. It is concluded that ICT have great influence on teaching and learning. Also, using ICT can improve teaching and learning processes.